Determining Factors Affecting the Users’ Participation of Online Health Communities: An Integrated Framework of Social Capital and Social Support - Tian, Xiu-Fu; Wu, Run-Ze (Frontiers in Psychology, 2022)
As the national awareness of health keeps deepening, OHCs(Online health communities) have achieved rapid development. Users' participation is critically important to the sustainable development of OHCs. Nevertheless, users usually lack the motive for participation. Based on the social capital theory, this research examines factors influencing users' participation in OHCs. The purpose of this research is to find out decisive factors that influence users' participation in OHCs, enrich the understanding of users' participation in OHCs, and help OHCs address the issue of sustainable development. The research model was empirically tested using 1277 responses from an online survey conducted in China. Data was analyzed using the structured equation modeling (SEM). We found informational support and emotional support to have significant direct effects over the structural capital, relational capital and cognitive capital of OHCs. Meanwhile, it is observed that relational capital and cognitive capital degree have a significant influence on knowledge acquisition and knowledge contribution of OHCs. For researchers this study provides a basis for further refinement of individual models of users’ participation. For practitioners, understanding the social capital is crucial to users’ knowledge acquisition and knowledge contribution that achieve high participation in OHCs.